Antibacterial and osteogenic activity of a multifunctional microporous coating codoped with Mg, Cu and F on titanium. Issue 14 (21st February 2019) - Zhao, Quanming; Yi, Lei; Hu, Annan; Jiang, Libo; Hong, Lin; Dong, Jian
Abstract : As preferred materials for bone tissue repair and replacement, titanium (Ti) and its alloys have been widely applied in clinical practice. Abstract : As preferred materials for bone tissue repair and replacement, titanium (Ti) and its alloys have been widely applied in clinical practice. However, since these materials are bioinert, synostosis cannot occur between these materials and natural bone. Therefore, modifying the surface of Ti with bioactive elements has been the subject of intense research. In the present study, a magnesium–copper–fluorine (Mg–Cu–F) codoped titanium dioxide microporous coating (MCFMT) was prepared on the surface of Ti by micro-arc oxidation (MAO). The coating had a micro/nanoporous structure and was uniformly doped with Mg, Cu and F. In vitro, the MCFMT could promote the adhesion, proliferation, differentiation, mineralization and apoptosis of MC3T3-E1 osteoblasts. In addition, MCFMT could inhibit the growth of Staphylococcus, providing a good antibacterial effect. Further studies showed that MCFMT promoted MAPK expression and might promote osteogenesis through ERK1/2 signaling. Therefore, establishing an MCFMT coating on the Ti surface is a feasible and effective way to improve the biological activity of Ti. This study provides a new concept and method for improving the biological activity of Ti and thus has important theoretical significance and potential applications.